Prevention of Pneumococcal Disease in Mice Immunized with Conserved Surface-Accessible Proteins - Hamel, Josée (Infect Immun, 2004)
The development of a vaccine against Streptococcus pneumoniae has been complicated by the existence of at least 90 antigenically distinct capsular serotypes. Common protein-based vaccines could represent the best strategy to prevent pneumococcal infections, regardless of serotype. In the present study, the immunoscreening of an S. pneumoniae genomic library allowed the identification of a novel immune protein target, BVH-3. We demonstrate that immunization of mice with BVH-3 elicits protective immunity against experimental sepsis and pneumonia. Sequence analysis revealed that the bvh-3 gene is highly conserved within the species. Since the BVH-3 protein shows homology at its amino-terminal end with other pneumococcal proteins, it was of interest to determine if protection was due to the homologous or to the protein-specific regions. Immunoprotection studies using recombinant BVH-3 and BVH-3-related protein fragments as antigens allowed the localization of surface-exposed and protective epitopes at the protein-specific carboxyl termini, thus establishing that BVH-3 is distinct from other previously reported protective protein antigens. Immunization with a chimeric protein comprising the carboxyl-terminal regions of BVH-3 and of a BVH-3-related protein improved the protection by targeting two surface pneumococcal components. Thus, BVH-3 and the chimeric protein hold strong promise as vaccine components to control pneumococcal disease.